International Congress for the study of the principles of a durable peace, Berne, 1916. The way out - Van Houten, S.; Central Organisation for a durable Peace (The Hague : Nijhoff, 1917)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: vredesinitiatieven; Wereldoorlog 1